Electron Acceleration in a Magnetotail Reconnection Outflow Region Using Magnetospheric MultiScale Data. Issue 1 (17th January 2020) - Eriksson, Elin; Vaivads, Andris; Alm, Love; Graham, Daniel B.; Khotyaintsev, Yuri V.; André, Mats
Abstract: We study Magnetospheric MultiScale observations in the outflow region of magnetotail reconnection. We estimate the power density converted via the three fundamental electron acceleration mechanisms: Fermi, betatron, and parallel electric fields. The dominant mechanism, both on average and the peak values, is Fermi acceleration with a peak power density of about +200 pW/m 3 . The magnetic field curvature during the most intense Fermi acceleration is comparable to the electron gyroradius, consistent with efficient electron scattering. The peak power densities due to the betatron acceleration are a factor of 3 lower than that for the Fermi acceleration, the average betatron acceleration is close to zero and slightly negative. The contribution from parallel electric fields is significantly smaller than those from the Fermi and betatron acceleration. However, the observational uncertainties in the parallel electric field measurement prevent further conclusions. There is a strong variation in the power density on a characteristic ion time scale. Key Points: The power density converted via the Fermi, betatron, and parallel electric field acceleration in a tailward reconnection jet is estimated The dominant electron acceleration mechanism is the Fermi acceleration in the current sheet center Significant variation in the power density is observed on the characteristic time scale of ions